11x-(-2x-11)=7+8x

Simple and best practice solution for 11x-(-2x-11)=7+8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x-(-2x-11)=7+8x equation:


Simplifying
11x + -1(-2x + -11) = 7 + 8x

Reorder the terms:
11x + -1(-11 + -2x) = 7 + 8x
11x + (-11 * -1 + -2x * -1) = 7 + 8x
11x + (11 + 2x) = 7 + 8x

Reorder the terms:
11 + 11x + 2x = 7 + 8x

Combine like terms: 11x + 2x = 13x
11 + 13x = 7 + 8x

Solving
11 + 13x = 7 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
11 + 13x + -8x = 7 + 8x + -8x

Combine like terms: 13x + -8x = 5x
11 + 5x = 7 + 8x + -8x

Combine like terms: 8x + -8x = 0
11 + 5x = 7 + 0
11 + 5x = 7

Add '-11' to each side of the equation.
11 + -11 + 5x = 7 + -11

Combine like terms: 11 + -11 = 0
0 + 5x = 7 + -11
5x = 7 + -11

Combine like terms: 7 + -11 = -4
5x = -4

Divide each side by '5'.
x = -0.8

Simplifying
x = -0.8

See similar equations:

| 0.10(x+200.00)=55.00 | | (x+4)/(3x+12)=0 | | x+5(x-2)=14 | | -3.2a=-5.68 | | 5x-11x=42 | | 2e^8x=7 | | 0.10(x+200.10)=100.00 | | x^2+26x+60=0 | | 3-6r=15 | | 4p+13p=85 | | 4(x-1)-(5x-8)=2(4x-1)-3 | | 5-5=13x+3x | | 1/3b-3=b+9 | | 24/7*8 | | 1-1=2(1-h) | | 1-1=1(1-h) | | b+(-3)=8 | | 4v^2-48v-52=0 | | 32=1y-8-13y | | 8-4p=4p-(10p-4) | | 9+4x=3x+6 | | -7(t-8)-2(2t+1)=-12 | | 5-14=z/-7 | | 7/5*1 | | 5/6(x-9)= | | 8-2(x-3)=10 | | 3+2x+4-2x=7 | | 2(3w-5)+2(w)=150 | | 4-3t/6t-8 | | 13+20=10x+27 | | x^4+17x^2+70=0 | | n-12.9/6.1=0.377 |

Equations solver categories